2019
DOI: 10.1021/acsami.9b14365
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification for Improving the Photocatalytic Polymerization of 3,4-Ethylenedioxythiophene over Inorganic Lead Halide Perovskite Quantum Dots

Abstract: Inorganic lead halide perovskite quantum dots (iLHP-QDs) have recently been used in the photocatalytic reaction. However, the factors that influence the photocatalytic performance of the iLHP-QDs have not been fully investigated. Herein, we synthesized a series of iLHP-QDs with varied halide ratios (CsPbX3, X = I, I0.67Br0.33, I0.5Br0.5, I0.33Br0.67, Br) and studied their influence on the photocatalytic performance by monitoring the polymerization of 2,2′,5′,2″-ter-3,4-ethylenedioxythiophene (TerEDOT). The CsP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…In a follow‐up study reported by Chen et al., they found that the performance of CsPbBr 3− x I x was enhanced upon increasing the iodine content (Figure c). Due to the narrow band gap and low exciton binding energy, CsPbI 3 QDs showed the best performance to accelerate the polymerization of TerEDOT.…”
Section: Engineering Mhps For Photocatalysismentioning
confidence: 99%
“…In a follow‐up study reported by Chen et al., they found that the performance of CsPbBr 3− x I x was enhanced upon increasing the iodine content (Figure c). Due to the narrow band gap and low exciton binding energy, CsPbI 3 QDs showed the best performance to accelerate the polymerization of TerEDOT.…”
Section: Engineering Mhps For Photocatalysismentioning
confidence: 99%
“…In here, an EDOT halide initially reacts with Mg to form the Grignard reagent. Afterwards, dibromo- or diiodoEDOT is added and a Ni(II) catalyst promotes the coupling to give terEDOT [ 54 , 55 , 56 , 57 , 58 , 59 ]. Kumada reaction was also applied to the synthesis of other unsubstituted EDOT-based trimers, such as thiophene-EDOT-thiophene [ 60 , 61 ] or EDOT-Thiophene-EDOT [ 62 , 63 ].…”
Section: Trimer Structuresmentioning
confidence: 99%
“…Nevertheless, direct modification of PNCs may be the most viable and straightforward option to accelerate the charge transport which therefore improves the photocatalytic performance efficiency. 41 To designing an efficient photo-catalyst the competition between radiative charge recombination and charge transfer remains the main focus. In the metal chalcogenides semiconductor nanocrystals, efficient charge separation was achieved through morphological and band engineering modifications via core/shell heterostructures.…”
Section: Introductionmentioning
confidence: 99%